(untitled) (Anwer Khan Modern Medical College Journal, 2012)
Primary renal squamous cell carcinoma is a very rare tumour. Only a few cases have been reported in world literature. Here we report a case with renal squamous cell carcinoma. The patient presented with flank pain, fever and vomiting. In ultrasonography, renal mass was detected and after nephrectomy followed by histopathological examination, it was diagnosed as squamous cell carcinoma. There was no evidence of renal calculi or other predisposing factors. This report highlights the rarity of the tumour. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11692 AKMMC J 2012: 3(2): 34-36